THE ROLE OF CYBER LAW IN PROTECTING INTELLECTUAL PROPERTY RIGHTS IN THE DIGITAL WORLD - Situmeang, Sahat Maruli Tua; Jatmika, Wishal Adya (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2024)
In the digital era, the development of information and communication technology has revolutionized human civilization, presenting both opportunities and challenges. Intellectual Property Rights (IPR) are critical to fostering creativity and innovation, but they face increasing threats in cyberspace, including piracy and unauthorized distribution. This research examines the role of cyber law in protecting IPR and identifies challenges in enforcing it, such as limited resources and rapid technological advances. Through normative legal research methods, including statutory and conceptual approaches, this research evaluates the existing legal framework and proposes solutions. Concrete steps include increasing resources, updating cyber laws to match technological advances, and raising public awareness through education and campaigns. In addition, multi-stakeholder collaboration involving government, academia, the private sector and civil society is essential for effective IPR protection in the digital era.